The Circus a Brief History of the Change of the Meaning of Circus – from a Ritual Experiment to an Experimental Show - Mielczarek, Rafał (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
This article is an attempt to analyse the change of the cultural meaning of the circus institution which took place during the long historical process of civilization evolution, affecting Western societies. The category of the sacred, the relation to which determined the cultural meaning of the circus, is crucial for this analysis. The change of meaning began from the original religious sources of the early forms of the games, when the circus was one of the ritual formulas used to celebrate socially significant events, and went through the secularisation of this formula during the domination of Christianity to the stage where the circus became a secular institution of mass entertainment.